Theoretical Foundations and Advantages of Teaching Natural Sciences Based on Steam Educational Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the theoretical foundations of teaching natural sciences based on STEAM education technologies, as well as the advantages of fostering students' creative thinking through this approach. It explores the methods, pedagogical value, and educational-technological aspects of implementing STEAM in science education, and highlights effective strategies for engaging students.